Regularity results for singular elliptic problems - Loredana Caso (Journal of Function Spaces and Applications)
Some local and global regularity results for solutions of linear elliptic equations in weighted spaces are proved. Here the leading coefficients are VMO functions, while the hypotheses on the other coefficients and the boundary conditions involve a suitable weight function.